DOI: 10.4018/978-1-5225-3023-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Polymer-Based Piezoelectric Systems

Abstract: Lately, polymer based piezoelectric materials that harness energy from mechanical vibrations and/or impact are being increasingly investigated as radical alternates to conventional batteries that are hard to service once deployed. Nevertheless, the optimization of energy outputs of piezoelectric energy harvesters is one of the prime challenges faced by the scientific community. This chapter provides an overview of polymer based piezoelectric energy harvesters with special emphasis on current state of research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…3,9 While there is an effort to mitigate both failures, late failures are difficult to treat in the clinic, and the attempts to revise these implants often result in a decreased likelihood of re-osseointegration. 10,11 By placing an emphasis on early failures, clinicians maximize preventative measures to mitigate both early and late implant loss, as all types of implant failures are often preceded by an early loss. 12,13 Early failures are often caused by several synergistic factors, such as surgical trauma, bacterial infiltration, or occlusal overload.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 While there is an effort to mitigate both failures, late failures are difficult to treat in the clinic, and the attempts to revise these implants often result in a decreased likelihood of re-osseointegration. 10,11 By placing an emphasis on early failures, clinicians maximize preventative measures to mitigate both early and late implant loss, as all types of implant failures are often preceded by an early loss. 12,13 Early failures are often caused by several synergistic factors, such as surgical trauma, bacterial infiltration, or occlusal overload.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency-dependent dielectric constant of the composite films can be explained by different types of polarization mechanisms with the application of electric fields such as electronic, ionic, dipolar and interfacial polarization. 30,31 It is found that for all composites, the dielectric constant decreases in the low frequency region, and then becomes more or less constant at higher frequency regions representing dielectric dispersion of the materials. The dielectric performance at lower frequency region may be attributed to the interfacial polarization.…”
Section: Dielectric and Electrical Properties Of Nbt-pvdf Composite Fmentioning
confidence: 94%